Analisis Perlindungan Konsumen Atas Penjualan Daging Hewan (Sapi dan Babi) di Pasar Mingguan Baun Menurut Undang Undang Perlindungan Konsumen Nomor 8 Tahun 1999 - Yoseph Imanuel Hawula; Darius Mauritsius; Yossie M.Y. Jacob (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This research was conducted at the Baun weekly market. The background to this research is markets that should provide quality, clean and halal food, however carrying out trade in animal meat that does not comply with sales standards. The problem studied is animal husbandry procedures in selecting livestock for farming slaughter at the baun market and the role of supervisor and responsibilities of the district livestock service Kupang, the role of breeders in terms of consumer protection regarding the sale of animal meat (Cow and Pork) at the baun market. This research uses empirical methods or methods with data obtained from direct interviews in the field. 1) Procedures for cattle breeders and pigs to be slaughtered according to procedures and supervised directly by the livestock service Kupang Regency and the quality of the meat produced is safe and high quality at the Baun market. 2) Supervision of animals and animal meat (beef and pork) is carried out by veterinarians, breeders, Kupang district livestock service, BPOM, health service, (LPPOM MUI), (BPKN), (LSPK), market foremen, and sub-district/district governments.